The last dinosaurs of Brazil: The Bauru Group and its implications for the end-Cretaceous mass extinction - BRUSATTE,STEPHEN L. (2017)
ABSTRACT The non-avian dinosaurs died out at the end of the Cretaceous, ~66 million years ago, after an asteroid impact. The prevailing hypothesis is that the effects of the impact suddenly killed the dinosaurs, but the poor fossil record of latest Cretaceous (Campanian-Maastrichtian) dinosaurs from outside Laurasia (and even more particularly, North America) makes it difficult to test specific extinction scenarios. Over the past few decades, a wealth of new discoveries from the Bauru Group of Brazil has revealed a unique window into the evolution of terminal Cretaceous dinosaurs from the southern continents. We review this record and demonstrate that there was a diversity of dinosaurs, of varying body sizes, diets, and ecological roles, that survived to the very end of the Cretaceous (Maastrichtian: 72-66 million years ago) in Brazil, including a core fauna of titanosaurian sauropods and abelisaurid and carcharodontosaurid theropods, along with a variety of small-to-mid-sized theropods. We argue that this pattern best fits the hypothesis that southern dinosaurs, like their northern counterparts, were still diversifying and occupying prominent roles in their ecosystems before the asteroid suddenly caused their extinction. However, this hypothesis remains to be tested with more refined paleontological and geochronological data, and we give suggestions for future work.